Training Teachers for Diversity Awareness: Impact on School Attendance of Refugee Children - Semih Tumen; Michael Vlassopoulos; Jackline Wahba (Institute of Labor Economics (IZA), 2021)
Despite efforts to integrate refugee children into host country education systems, their low school attachment remains a major policy challenge. Teachers play a key role in keeping students attached to school, yet classroom diversity poses difficulties for teachers who are not always adequately prepared to address the needs of minority students. Using administrative data and a regression discontinuity approach, we evaluate whether a teacher training program—designed to raise awareness of primary and secondary school teachers in Turkey—is effective in reducing absenteeism of refugee students. We find that the program almost halves the absenteeism gap between native and refugee students and its effect persists into the next academic year, albeit fading out in size. We argue that the most likely channel through which the effects of the program operate is a school-wide mentorship role acquired by trained teachers, which has broad impact on raising diversity awareness within schools.
Keywords: I21; I28; J15; 330; teacher training; refugees; absenteeism; diversity